Integrating Multicultural Education Through Experiential Learning: Insights from the Nusantara Mini Expo at Elementary School - Riski Sumaryanto; Woro Sri Hastuti; Aniela Calista Deadema; Gantheng Listyoadi; Rashika Ardafa Sahila; Celine Widyaningrum Kusumawardani (STAI Hubbulwathan Duri, 2025)
This study investigates the implementation of multicultural education through experiential learning, specifically in the context of the Nusantara Mini Expo held at elementary schools. The research focuses on how direct cultural engagement fosters students’ understanding of Indonesia’s cultural diversity. A qualitative case study approach was employed, using data collected through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model to ensure validity and reliability. Findings reveal that the Nusantara Mini Expo serves as an effective platform for multicultural education. Through direct interaction with various cultural elements—such as traditional clothing, art, music, and cuisine—students gain a deeper, more personal understanding of Indonesia’s diverse heritage. The experience-based model fosters sensory and emotional engagement, which enhances cultural appreciation and awareness. This participatory approach transforms multicultural education from a theoretical concept into a lived experience. By integrating cultural elements into interactive learning activities, the expo encourages empathy, respect, and inclusivity among students. The study underscores the educational value of connecting learners with culture in meaningful and memorable ways. The research highlights the importance of incorporating experience-based multicultural education into the elementary curriculum. Such integration promotes cultural identity, tolerance, and mutual respect—crucial competencies in an increasingly globalized world.